Analysis Of Stock Price Determinants In Islamic Banks In Indonesia - Miftha Farild; Anggi Somba Poddala; Azizah Saban (International Journal of Economics and Management Sciences, 2024)
This study aims to determine and analyze stock prices by looking at the direct and indirect effects between inflation, interest rates, exchange rates, ROA and stock prices in Islamic Banks in Indonesia. This study uses panel data regression with variables of inflation, interest rates, exchange rates, ROA, and stock prices with data analysis using SPSS 22 software. The period of this study is 2020-2022. The results of this study indicate that inflation, interest rates, and exchange rates are significant to ROA. Inflation and ROA are directly significant to stock prices. Meanwhile, interest rates and exchange rates directly have no effect on stock prices. For the indirect relationship between inflation, interest rates, and exchange rates affect stock prices through ROA.